Influence of COVID-19 on depression and anxiety (International Seven Journal of Multidisciplinary, 2024)
COVID-19 is an acute respiratory infection caused by the coronavirus SARS-CoV-2, potentially serious, highly transmissible and globally distributed. The consequences of the human body's exposure to the virus have been a focus of great interest for the scientific community. This study aimed to evaluate the effects of COVID-19 on depression and anxiety, with the aim of verifying the presence or absence of worsening of these neuropsychiatric diseases as a result of virus infection. To this end, the tool used was a questionnaire with 16 closed and open questions on the topic, prepared through the Google Forms platform, which was made available through the social networks WhatsApp, Instagram and Facebook, becoming available between the months of February and December of 2022. The questionnaire included questions related to the patient's clinical condition as well as whether or not anxiety and depression worsened. A total of 70 people met the inclusion criteria and responded to the questionnaire, of which 64.29% were diagnosed with anxiety, 10% with depression and 25.71% with both conditions. Of these, 55.71% persisted with neuropsychiatric conditions and were undergoing treatment, while 27.14% were without treatment and 17.14% had their treatments completed. The most effective treatments involved psychotherapy associated with pharmacological therapy. The worsening of symptoms in the post-infection period was 62.86%. An increase in the dosage of psychotropic medications was observed in 87.8% of cases, with the most serious cases being related to the time of infection and possible deleterious effects of the virus on the CNS. The results together corroborate data from the literature on the worsening of psychiatric conditions due to COVID-19.